Analytical study on secondary metabolites extraction and characterization from Acacia gums (AGs) - Elnour, Ahmed A. M.; Al-Assaf, Saphwan; Kabbashi, Nassereldeen Ahmed; Osman, Mohammed Elmubark; Abdelgadir, Abdelgadir Elfadil (Springer, 2025)
Acacia gums (AGs), derived from Acacia senegal, Acacia seyal, and Acacia polyacantha trees, are widely used in various industries, including food, pharmaceuticals, and cosmetics. They serve as emulsifiers, stabilizers, thickeners, and soluble dietary fibers. This study aimed to optimize the extraction process of secondary metabolites extracted (SME) from AGS to enhance their efficiency and quality for industrial applications. Gum arabic, primarily composed of D-galactose, L-arabinose, L-rhamnose, D-glucuronic acid, and 4-O-methyl-D-glucuronic acid with a small fraction of proteins, is a multifunctional ingredient known for its emulsifying activity, attributed to its amphiphilic nature. Its effectiveness as an emulsifier stems from its high water solubility, low-viscosity, good surface activity, and ability to form a protective film around emulsion droplets. AGS in Sudan play crucial ecological roles by providing fodder, firewood, gums, and soil erosion control, which are essential for gum arabic production. Sudan’s diverse biodiversity hosts many plant species traditionally used for medicinal purposes, with extensive knowledge of medicinal plant species stemming from their widespread use among different ethnic groups. This study highlights the importance of optimizing the extraction of secondary metabolites from AGS for industrial applications, and the significance of AGS in Sudan’s ecological balance and economic stability.